Accounting for Proprietary Research. - Drebin, Allan R. (The Accounting Review, 1966)
The article focuses on the trend of corporations funding extensively for research to improve upon their profit margins. It is estimated that business units in the U.S. are spending nine billion dollars annually on research activities. Firms in some industries such as pharmaceuticals, chemicals, and electronics depend upon research for their survival, and it is not uncommon to find companies in these fields spending more for research each year than their reported earnings. Since these expenditures have reached extreme proportions, the accounting treatment of research costs has become a vitally important factor in determining the income of the companies involved. It is concluded that the procedures currently used in accounting for research and development do not present a realistic picture of the economic consequences of this activity. They also are inconsistent with the principles which are generally applied to other areas of accounting. In addition, they provide management with an incentive for cutting back research expenditures although such curtailment might have a deleterious effect upon the long-range position of the company.